Liquid Ventilation - Peter N Cox (Canadian Respiratory Journal)
There has been a recent explosion of interest in the use of liquid ventilation. Over time humans have lost the physiological attributes necessary for respiration in water. However, perfluorocarbons have high solubilities for oxygen and carbon dioxide, as well as a low surface tension. These characteristics allow them to be used as a medium to assist gas exchange and recruit atelectatic-dependent lung zones in respiratory distress syndrome. Current trials may prove perfluorocarbon to be a useful adjunct in lung protective strategies in respiratory distress syndrome.